2022
DOI: 10.1038/s42003-022-03335-7
|View full text |Cite
|
Sign up to set email alerts
|

Control of carbon monoxide dehydrogenase orientation by site-specific immobilization enables direct electrical contact between enzyme cofactor and solid surface

Abstract: Controlling the orientation of redox enzymes on electrode surfaces is essential in the development of direct electron transfer (DET)-based bioelectrocatalytic systems. The electron transfer (ET) distance varies according to the enzyme orientation when immobilized on an electrode surface, which influences the interfacial ET rate. We report control of the orientation of carbon monoxide dehydrogenase (CODH) as a model enzyme through the fusion of gold-binding peptide (gbp) at either the N- or the C-terminus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Therefore, the configuration of heme enzymes in a monolayer, for example, needs to be orientated to minimize the distance between the heme center and electrode (within 14 Å) as a so-called ''electroactive'' configuration. [209][210][211] HRP, for example, has a molecular radius of 30 Å 212 that would block the direct electron transfer, since the heme sites buried in the protein frameworks may be too far away from the electrode. Previous literature suggested that the selectivity and stability of enzymes can also be controlled by varying the orientation of enzymes on the electrode surface.…”
Section: Activation Of Cyt P450smentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the configuration of heme enzymes in a monolayer, for example, needs to be orientated to minimize the distance between the heme center and electrode (within 14 Å) as a so-called ''electroactive'' configuration. [209][210][211] HRP, for example, has a molecular radius of 30 Å 212 that would block the direct electron transfer, since the heme sites buried in the protein frameworks may be too far away from the electrode. Previous literature suggested that the selectivity and stability of enzymes can also be controlled by varying the orientation of enzymes on the electrode surface.…”
Section: Activation Of Cyt P450smentioning
confidence: 99%
“…Adding a short electrode-binding peptide at a specific terminal of enzymes can guide the binding direction of enzymes to the electrode and avoid the non-specifical orientation of enzymes. 209 This method can provide the oriented immobilization of Cyt P450s. 234 P450 BM3 C-terminally high specific peptide (HSP), as an example can be immobilized on an ITO electrode binding peptide (HSP) made of sequence (RTRHK) 4 .…”
Section: Activation Of Cyt P450smentioning
confidence: 99%
“…Effects of design factors on performance parameters References SBP fusion site Catalytic activity ✓ Catalytic activity of enzyme tends to be highly preserved after genetic SBP fusion. [29,34,44] Inorganic-binding activity ✓ SBP fusion to multiple sites can increase overa ll inorganic-binding affinities. ✓ The external exposure degree of fusion site (i.e., C-or N-terminus of protein structure) can determine contact probability of SBP domain with target surfaces.…”
Section: Design Factors Performance Parametersmentioning
confidence: 99%
“…[ 27 ] Therefore, to achieve intimate, direct electrical coupling between redox enzymes and electrodes, the enzyme must be oriented on the electrode such that its active site is near the metallic surface. [ 28,29 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation